Biopetrol synthesized from rubber seed oil by zeolites catalyst : effect of operating temperature in cracking process - Mohd Azwan, Mohd Saderi (2012)
Petroleum is a fossil fuel which takes millions of years to form.The fossil fuel that used today depleting much faster without suspected.The alternatives fuel must be searched to solve this problems.The rubber seed oil is found to be a promising alternative fuel source to replace petrol fuel. Biopetrol is derived from vegetable oil and also renewable energy source.The objectives of this research are to synthesize biopetrol from rubber seed oil in order to overcome fuel supply problem and to identify the effect of temperature in cracking process using zeolites catalyst for the rubber seed oil production.Soxhlet extractor is used to extract the rubber seed oil from the rubber seed.Then,the hexane is removed by using rotary evaporator to get pure rubber seed oil.The catalytic cracking with presence zeolites as the catalyst is applied to crack the fatty acid complex into smaller hydrocarbon molecules.Five grams of zeolites catalyst is added into the crucible that contain 25 ml rubber seed oil.The mixture is heated in the furnace at 300°C for 15 minutes.After that,the different temperature is used which is 350°C and 400°C in order to see the effect of temperature on the isooctane production.By using the gas chromatography,the presence of isooctane in the sample can be detected which is indicate that biopetrol is produced. Based on this research,the highest amount of isooctane is produced which is 75.3234% at temperature of 350ºC.The presence of temperature and catalyst that used will give the sudden effect to production of isooctane from the rubber seed oil.In conclusion,biopetrol can be produced from the rubber seed oil by zeolites catalyst.